Anthropological assumptions on the comprehensive human development as an ethical life project under the light of the caritas in veritate encyclical - Gómez Navarro, Ángel (2010)
To achieve comprehensive human development is the fundamental ethical challenge that the contemporary man must undertake as true ethical life project to responsibly seek unity and the sense of existence. This paper explores the likelihood conditions of this comprehensive selfachievement dynamic project, such as the willingness to be open to what is transcendent, the dialogic or intersubjective relationship, the freedom of self-determination, the ethical discernmentand the responsible commitment.